Penanaman Nilai Agama dan Moral pada Anak Usia Dini Perspektif Peran Orang Tua - Setya Murni; Dewi Ariyani (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2022)
Currently, there is a rise in the number of reports about violence and nonconformities committed by young children. This condition is very worrying, considering that the world of children should be playing and learning.  The purpose of this study is to describe the inculcation of religious and moral values in early childhood from the perspective of the role of parents and the values that are instilled in early childhood in Panisihan Village, Maos District, Cilacap Regency. This research is field research with a qualitative descriptive approach. Data collection methods used are observation, interviews, and documentation. Data analysis techniques used are data reduction, data display, and conclusion drawing. The results showed that parents play an important role in instilling religious and moral values in early childhood. Parents represent as instructors, motivators, models, and supervisors. The inculcated religious and moral values are prayer, honesty, discipline, respect for others, and social concern